مقاربة سوسيو-تحليلية لمفهوم المواطنة في خضم العلاقة التليدة مع العلوم الاجتماعية - بن الطاهر, حمزة (جامعة الوادي - University of Eloued, 2021)
يعد مفهوم المواطنة من المفاهيم الحديثة ارتبطت بسياقات فكرية عديدة؛ سياسية وثقافية واجتماعية، تناولها المفكرون والباحثون كجوهر وجود المجتمعات واستقرارها و علا مدلولها في تراتبية الأهمية والضرورة لدى جل المجتمعات الحديثة، لما ارتبط بها من ظواهر جديدة وأخرى متجددة، ولان المواطنة قيم مكتسبة لها العلاقة الكاملة بالتنشئة الاجتماعية للأفراد، أفتكت العلوم الاجتماعية الدور المهم والأساس في عملية تجذذرها وترسيخها وحمايتها.. والورقة البحثية دراسة نظرية تسعى لإيجاد مقاربة تحليلية بين العلوم الاجتماعية والمواطنة في الجزائر، ومحاولة ربط العلاقة بين أركان الثالوث: العلوم الاجتماعية، التنشئة الاجتماعية، المواطنة. The concept of citizenship considered among modern concepts, associated with many cultural, political, cultural and social contexts, addressed thinkers and researchers as the essence and existence of communities, stability and increased its concept in echelon importance and need of most modern societies, which has been associated with new and other renewable phenomena, and if that citizenship has acquired its relational values full socialization of individuals, the social sciences takes its role .important and fundamental in rooting and process and its consolidation and protection The document is a theoretical study seeking to find an analytical approach between the social sciences and citizenship in Algeria, and the attempt to link the relationship between the pillars of the Trinity: the social sciences socialization citizenship.
Socio-analytical approach to the concept of citizenship within the ancient relationship with social sciences
مقال
Keywords: العلوم الاجتماعية ، التنشئة الاجتماعية، المواطنة; social sciences, socialization, citizenship